PEMBENTUKAN KARAKTER ANAK USIA DINI MELALUI PERMAINAN TRADISIONAL - Hendar Hendar; Heri Heryono; Ida Zuraida; Atri Nadia Astarina; Meita L. Sujatna (Jurnal Abdimas Bina Bangsa, 2023)
As technology advances, traditional games are becoming less common, and children are spending more time indoors with digital devices. This shift raises concerns about the impact on a child's physical, social, and emotional development. Based on these facts, this Community Service program was held with the aim of increasing the understanding and awareness of Early Childhood Education (PAUD) teachers about traditional games in building early childhood character. This activity was carried out by involving 100 PAUD teachers in Cikaum Subdistrict, Subang. This program begins with the distribution of questionnaires to see preliminary data related to the understanding and awareness of ECCE teachers regarding the use of traditional games as one of the supports for the process of teaching and learning activities in the classroom, especially with its relation to building children's character. Data shows that the majority of ECCE teachers in Cikaum Subdistrict, Subang quite understand and realize the benefits of traditional games in shaping children's character. This is supported by data where 100% of participants apply traditional games in the process of teaching and learning activities in the classroom